SARS‐CoV‐2‐specific CD8+ T‐cell responses and TCR signatures in the context of a prominent HLA‐A*24:02 allomorph. Issue 9 (30th June 2021) - Rowntree, Louise C; Petersen, Jan; Juno, Jennifer A; Chaurasia, Priyanka; Wragg, Kathleen; Koutsakos, Marios; Hensen, Luca; Wheatley, Adam K; Kent, Stephen J; Rossjohn, Jamie; Kedzierska, Katherine; Nguyen, Thi HO
Abstract: In‐depth understanding of human T‐cell‐mediated immunity in coronavirus disease 2019 (COVID‐19) is needed if we are to optimize vaccine strategies and immunotherapies. Identification of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) T‐cell epitopes and generation of peptide–human leukocyte antigen (peptide–HLA) tetramers facilitate direct ex vivo analyses of SARS‐CoV‐2‐specific T cells and their T‐cell receptor (TCR) repertoires. We utilized a combination of peptide prediction and in vitro peptide stimulation to validate novel SARS‐CoV‐2 epitopes restricted by HLA‐A*24:02, one of the most prominent HLA class I alleles, especially in Indigenous and Asian populations. Of the peptides screened, three spike‐derived peptides generated CD8 + IFNγ + responses above background, S1208–1216 (QYIKWPWYI), S448–456 (NYNYLYRLF) and S193–201 (VFKNIDGYF), with S1208 generating immunodominant CD8 + IFNγ + responses. Using peptide–HLA‐I tetramers, we performed direct ex vivo tetramer enrichment for HLA‐A*24:02‐restricted CD8 + T cells in COVID‐19 patients and prepandemic controls. The precursor frequencies for HLA‐A*24:02‐restricted epitopes were within the range previously observed for other SARS‐CoV‐2 epitopes for both COVID‐19 patients and prepandemic individuals. Naïve A24/SARS‐CoV‐2‐specific CD8 + T cells increased nearly 7.5‐fold above the average precursor frequency during COVID‐19, gaining effector and memory phenotypes. Ex vivo single‐cell analyses of TCRαβ repertoires found that the A24/S448 + CD8 + T‐cell TCRαβ repertoire was driven by a common TCRβ chain motif, whereas the A24/S1208 + CD8 + TCRαβ repertoire was diverse across COVID‐19 patients. Our study provides an in depth characterization and important insights into SARS‐CoV‐2‐specific CD8 + T‐cell responses associated with a prominent HLA‐A*24:02 allomorph. This contributes to our knowledge on adaptive immune responses during primary COVID‐19 and could be exploited in vaccine or immunotherapeutic approaches. Abstract : Analysis of unmanipulated SARS‐CoV‐2‐specific CD8 + T cells was performed by direct ex vivo tetramer staining in COVID‐19 patients. We investigated in‐depth SARS‐CoV‐2‐specific CD8 + T‐cell responses and their T‐cell receptor (TCR) signatures restricted by a prominent HLA‐A*24:02 allomorph.